The religious aspects of Turkic dastans - Aлжaнбaевa У. Т.,; Зaировa Н. Ш. (Journal of Oriental Studies, 2018)
This article seeks to examine the influence of religious motives in Turkish dastans, especially the example of «Қissa Hazіret Zhүsіp Әleyһissalam Ilәn Zylihanyң mәselesі».The author explores the religious aspects of the conceptual – semantic vision based on three main books: Ғashyқ – Namе, the Holy Quran and the Bible. An author analyses connections and cooperation of one personage: his fate and historical meaningfulness on the joint of two religions. There are comparison of role of personage from the side of mental and ethical values and influence of succession in turkic dastans.